1992
DOI: 10.1007/bf01046330
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent (early onset) schizophrenia: A review in light of DSM-III-R

Abstract: Early onset schizophrenia (EOS) is defined as that beginning in childhood or adolescence (under 16 or 17). Studies of EOS are infrequent, and comparative adult figures not always available, but tentative conclusions may be drawn. EOS is more common in males; symptomatology is often undifferentiated; frequencies of homotypic family disorder, premorbid schizotypal personality, and neurodevelopmental abnormalities high; outcome poor but only slightly worse than in adults; response to psychotropic drug treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
2
13

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 35 publications
8
103
2
13
Order By: Relevance
“…38 Although very-early onset schizophrenia is rare, Green et al . examined 38 children with schizophrenic disorder who were younger than 12 years of age, and indicated that catatonia or other grossly disorganized behavior was present in 12 (31.6%) of the 38 cases.…”
Section: Schizophrenia and Other Psychotic Disordersmentioning
confidence: 99%
“…38 Although very-early onset schizophrenia is rare, Green et al . examined 38 children with schizophrenic disorder who were younger than 12 years of age, and indicated that catatonia or other grossly disorganized behavior was present in 12 (31.6%) of the 38 cases.…”
Section: Schizophrenia and Other Psychotic Disordersmentioning
confidence: 99%
“…It has been estimated that approximately 4 % of all schizophrenia patients have their illness onset before 18 years of age [14], which is termed early-onset schizophrenia (EOS) [84]. Childhood-onset of schizophrenia (COS, onset by age 12) [39] is extremely rare [12;80], whereas the incidence increases between the ages 13 to 17 years [70 ;80].…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between autism and schizophrenia becomes particularly unclear when little or no positive symptoms are present (Werry, 1992). Several studies reported overlap in negative symptoms between the two disorders (Dykens, Volkmar, & Glick, 1991;Konstantareas & Hewitt, 2001;Petty, Ornitz, Michelman, & Zimmerman, 1984;Sheitman, Bodfish, & Carmel, 2004;Spek & Wouters, 2010).…”
mentioning
confidence: 99%